Mississippi Civil War Monuments : An Illustrated Field Guide - Sedore, Timothy S. (Timothy Stephen) (Book collections on Project MUSE., 2020)
"In soaring obelisks, graceful arches, and soldiers standing tall atop pedestals, the memory of the Civil War is ever present in Mississippi, a former Confederate state that boasts more Civil War monuments than any other. In Mississippi Civil War Monuments: An Illustrated Field Guide, Timothy S. Sedore combs through the Mississippi landscape, exploring monuments commemorating important military figures and battles and remembering common soldiers, from rugged veterans to mournful youths. Sedore's insightful commentary captures a character portrait of Mississippi, a state that was ensnared between Northern and Southern ideologies and that paid a high price for seceding from the Union. Sedore's close examinations of these monuments broadens the narrative of Mississippi's heritage and helps to illuminate the impacts of the Civil War. With intriguing details and vivid descriptions, Mississippi Civil War Monuments offers a comprehensive guide to the monuments that make up Mississippi's physical and historical landscape."